Characteristics of microsporidial keratoconjunctivitis in an eastern indian cohort: A case series - Jayangshu Sengupta; Suman Saha; Archana Khetan; Dipanjan Pal; Nibaran Gangopadhyay; Debdulal Banerjee (Wolters Kluwer Medknow Publications, 2011)
Background: Microsporidia are intracellular parasites responsible for human infections. Recently, there has been an increase in the incidence of microsporidial keratoconjunctivitis (MKC) affecting normal individuals worldwide. Aim: To determine the characteristics of MKC in an Indian cohort. Materials and Methods: This is a retrospective, noncomparative, observational case series, involving patients with MKC between June and September 2009. Of the 24 patients identified, microbiological confirmation in direct smear was obtained in 22 cases and selected. Standard microbiological workup was performed in all the cases. We studied the demographics, predisposing conditions, antecedent treatment received before presentation, clinical characteristics, treatment offered, and resolution time with sequel. The management consisted of simple debridement and application of chloramphenicol ointment (1%) two times a day. Results: Mean age of onset was 18.7 years (95% CI, 15.7-21.7; range, 11-36s years). All patients gave history of prior outdoor activity and exposure to rain water/mud. Antecedent treatment comprised of Acyclovir eye ointment (45.4%) and antibiotic eye drop (27.3%) most commonly. Microsporidia were identified in Gram stain (81.8%), 10% potassium hydroxide mount (72.7%), modified Ziehl-Neelsen staining (36.4%), and Giemsa (18.2%). Majority presented as unilateral superficial keratoconjunctivitis with punctate epithelial keratitis. Mean resolution time was 9 days (95%CI, 7.9-10.2). Conclusions: MKC can occur in normal patients with exposure to rain and mud, related to outdoor activity often misdiagnosed as viral ocular infections. Strong clinical suspicion with proper microbiological evaluation helps to diagnose this commonly misdiagnosed condition.